A Review of Trends in the Automation of Advertising Processes on Marketplaces with an Emphasis on ThinkAd’s AI Solutions - Dmytro Balan (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This paper covers the history and current trends in the automation of advertising workflow within marketplaces through AI solutions provided by the ThinkAd platform. The study shall attempt to detail drivers that have prompted a transition from manual bidding to intelligent autopilots. It also tries to present comparative analyses regarding the functionalities of leading AI services and empirical assessments of their effectiveness via real-world case studies. Such a work is meaningful since there has been a strong upward trend in cost-per-click on Amazon Ads, coupled with increasing difficulties that come with manual management regarding hundreds of thousands of product × keyword × time combinations, which cause both budget overruns and lost sales. Simultaneously, first-party data gains value in a cookieless world; intense competition demands instant strategy changes via hyper-personalization and goal-based bidding. The novelty of the study lies in the integration of descriptive statistics on CPC dynamics and sellers’ time savings, content- and case-analysis of AI-platform technical documentation, and a functional comparison of semantic-core generation modules, goal-based bidding, hourly day-parting, and multi-account mastering. Particular attention is paid to the ThinkAd platform, which forecasts ACoS 24 hours in advance, updates bids hourly, and consolidates data across multiple stores. The main findings indicate that intelligent automation can reduce ACoS to 22–25% while increasing advertising sales by 82–206%, freeing up to 20 hours of operational time per week, and ensuring competitiveness for small and medium enterprises under cookieless conditions and rising click costs. Integrated via the Amazon Ads API and supporting multiple regions, ThinkAd sets a new efficiency standard by combining a semantic module, predictive analytics, and an autopilot. This article will be helpful to marketplace advertising managers, e-commerce analysts, and small and medium business owners when selecting and implementing AI tools for advertising campaign automation.